Virtue Ethics, Character, and Normative Receptivity - Upton, Candace (2008)
Abstract Classically-conceived accounts of character posit traits that are both dynamic and global. Dynamic traits produce behavior, and global traits produce behavior across the full range of situation kinds relevant to a particular trait. If you are classically just, for example, you would behave justly across the full range of situation kinds relevant to justice. But classical traits are too crude to fulfill trait attributions' intrinsically normative purpose, which is to reflect the moral merit agents deserve. I defend an extra-classical account of character traits that endorses flexible traits that might issue in behavior across any narrow or broad range of situation kinds, and static traits that might issue in no behavior at all. Extra-classical traits are more subtle and sensitive, and so are normatively receptive to the credit that psychologically-complicated agents merit. Further, extra-classical traits can fulfill all the unproblematic roles of classical traits. Extra-classicism is, hence, a significant and substantial improvement upon classically conceived character traits and traditional virtue ethics.
Keywords: BEHAVIOR; Virtue; Character; Ethics